Accurate direct power control for dual active bridge converter in DC microgrid - YE Yulin; YU Ting; LIU Chen; SUN Hui; XIAO Zhongxiu (Xi'an Gongcheng Daxue xuebao)
In the DC microgid, aimed at the power flow problem of dual active bridge (DAB) converters and their connected energy storage systems, this paper proposed an accurate direct power control (ADPC) method. The introduced control approach ensured constant power transmission on both sides of the DAB converter and was characterized by high accuracy, fast dynamic response, and excellent stability. It overcame the limitations of traditional direct power control (DPC) methods, which were highly dependent on system parameters. The effectiveness of the ADPC method was verified through simulations using MATLAB/Simulink and real-world experimental platforms. When compared to traditional power PI control methods, the proposed ADPC mtehod, according to simulation and experimental results, significantly improves the dynamic performance of output power, especially under conditions of abrupt changes in power setpoints, load shifts, and input voltage fluctuations. Moreover, the method is independent of system parameters, enhancing the control method's compatibility and portability. The proposed method shows promising application prospects in the field of electric energy dispatch control within DC power supply networks.